Recent Investigations at Two Long Barrows and Reflections on their Context in the Stonehenge World Heritage Site and Environs - David Roberts; Andrew Valdez-Tullett; Peter Marshall; Jonathan Last; Alastair Oswald; A. Barclay; B. Bishop; E. Dunbar; Alice Forward; Matt Law; N. Linford; Paul Linford; et al. (Internet Archaeology, 2018)
Recent geophysical surveys and excavations at Druid's Lodge Estate, in fields west of the Diamond Wood in the Stonehenge World Heritage Site (SWHS), have confirmed the existence of the Winterbourne Stoke 71 long barrow and discovered a new long barrow (Winterbourne Stoke 86) a short distance to the south. Survey and excavation show internal features at both barrows and, alongside aerial photography, suggest that both monuments were destroyed during later prehistory. These barrows are part of a cluster around the head of the Wilsford dry valley. We review long barrows in the SWHS and environs to contextualise these discoveries, demonstrating a diversity of internal features, barrow sizes and morphologies. Chronological modelling is used to place the SWHS barrows in their inter-regional timescape and to understand the timings of the first appearance of monument types of the 4th millennium cal BC. Local topography appears to be the key factor in determining the alignment of long barrows, but the eastern ends of barrows appear to be significant. Long barrows are also considered in relation to causewayed enclosures, and movement around the landscape. Long barrows are an important structuring monument in the later Neolithic and Bronze Age landscape, but their importance is mediated by their location relative to Stonehenge, and access to the monument from the south. There is a clear pattern of differential preservation of long barrows away from the vicinity of Stonehenge. Further field research is necessary to achieve a better understanding of long barrows in the SWHS, and it is hoped that this article stimulates interest in these highly significant monuments. This article also provides an interactive map of the SWHS, linking to simplified plans of long barrows in the study area, additional information and references for further reading for each barrow. Appendices are provided containing specialist methodologies and/or data from the geophysical surveys and the Historic England excavation, and primary excavation data from the Historic England excavation is downloadable via the Archaeology Data Service (Historic England 2018).